A Hierarchical Short Microneedle-Cupping Dual-Amplified Patch Enables Accelerated, Uniform, Pain-Free Transdermal Delivery of Extracellular Vesicles - Song, Minwoo; Ha, Minji; Shin, Sol; Kim, Minjin; Son, Soyoung; Lee, Jihyun; Hwang, Gui Won; Kim, Jeongyun; Duong, Van Hieu; Park, Jae Hyung; Pang, Changhyun (Nano-Micro Letters, 2025)
Microneedles (MNs) have been extensively investigated for transdermal delivery of large-sized drugs, including proteins, nucleic acids, and even extracellular vesicles (EVs). However, for their sufficient skin penetration, conventional MNs employ long needles (≥ 600 μm), leading to pain and skin irritation. Moreover, it is critical to stably apply MNs against complex skin surfaces for uniform nanoscale drug delivery. Herein, a dually amplified transdermal patch (MN@EV/SC) is developed as the stem cell-derived EV delivery platform by hierarchically integrating an octopus-inspired suction cup (SC) with short MNs (≤ 300 μm). While leveraging the suction effect to induce nanoscale deformation of the stratum corneum, MN@EV/SC minimizes skin damage and enhances the adhesion of MNs, allowing EV to penetrate deeper into the dermis. When MNs of various lengths are applied to mouse skin, the short MNs can elicit comparable corticosterone release to chemical adhesives, whereas long MNs induce a prompt stress response. MN@EV/SC can achieve a remarkable penetration depth (290 µm) for EV, compared to that of MN alone (111 µm). Consequently, MN@EV/SC facilitates the revitalization of fibroblasts and enhances collagen synthesis in middle-aged mice. Overall, MN@EV/SC exhibits the potential for skin regeneration by modulating the dermal microenvironment and ensuring patient comfort. Highlights: 1 A bio-inspired dual-amplified patch (MN@EV/SC) was fabricated by integrating extracellular vesicle-loaded microneedles with a soft suction chamber for effective transdermal delivery. 2 The MN@EV/SC system achieved an exceptional penetration depth of 290 μm, while minimizing plasma corticosterone levels with short microneedles, ensuring patient comfort through pain-free application. 3 This system showed the potential for dermatological application by revitalizing dermal fibroblasts, and enhancing collagen synthesis through effective delivery of extracellular vesicles while preserving their biological functionality.